Subversive justice: the Russell Vietnam War Crimes Tribunal and transitional justice - Zunino, Marcos (International journal of transitional justice, 2016)
In 1967, philosopher Bertrand Russell set up an unofficial war crimes tribunal to investigate the actions of the US in Vietnam. This article explores the link between the Russell Tribunal and transitional justice. In recent years, critical voices have called for a transitional justice that is less legalistic and state-centric and more concerned with socioeconomic issues. The Russell Tribunal was an early instance of a transitional justice practice whose traits resonated with these critiques. It challenged legalism, breached the judicial monopoly of the state and criticized the economic global order. Given this affinity, the Russell Tribunal can provide critical approaches to transitional justice with a historic antecedent and a mechanism to push their agenda forward. Unofficial tribunals, inspired by the Russell initiative, can be useful tools for a transitional justice that is broader and more amenable to alternative perspectives.